STRATEGI KOMUNIKASI SIARAN TVRI SUMATERA SELATAN SEBAGAI TELEVISI PUBLIK - Dina Novita; Yenrizal yenrizal; Badarudin Azarkasyi (Jurnal Prodi Ilmu Komunikasi, 2022)
This thesis aims to examine the "Communication Strategy for South Sumatra TVRI Broadcasting as Public Television". The background of the discussion in this thesis is the consistency of the South Sumatra TVRI media as public television. The research that the author uses is field research with qualitative methods and data collection through: observation, interviews, and documentation with the concept of communication strategy. The results of the South Sumatra TVRI Broadcasting Communication Strategy as a Public Television is done by making a plan which begins with determining the concept of goals, targets to be achieved, and the results to be obtained. Then monitoring and evaluation of the results of all these plans is carried out. In this process, TVRI South Sumatra compiles and coordinates together in a perfect concept of what achievements will be obtained from the program that has been conceptualized previously so that if the achievement concept is successful in achieving its goals, the designs and targets that have been previously in accordance with the final result. However, if the concept of achievement is not successful in achieving its goals, then the design and targets that have been there previously are not in accordance with the final results or in the sense that they fail to achieve their goals.